2021
DOI: 10.1093/dote/doab052.555
|View full text |Cite
|
Sign up to set email alerts
|

555 Visceral Obesity: Prevalence, and Impact on Operative and Oncologic Outcomes in the Curative Management of Esophageal Cancer

Abstract: Obesity, in particular visceral obesity, is a risk factor for esophageal cancer, but its prevalence and impact on operative and oncologic outcomes is unclear. The aim of this study was to study adipose distribution in esophageal cancer (EC), and to assess its independent impact. Methods 11 consecutive patients undergoing treatment with curative intent for esophageal cancer were studied. Total (TFA), subcutaneous (SFA) and visceral fat areas (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 0 publications
8
48
0
Order By: Relevance
“…This is at odds with recently published meta‐analyses that show that preoperative sarcopenia is an independent unfavorable prognostic factor for oesophageal and gastric cancer patients after oesophagectomy and gastrectomy 54,55 . Nevertheless, there is conflicting evidence from multiple studies that, similar to us, have been unable to find an association between sarcopenia and postoperative outcomes in an OG cancer cohort undergoing curative therapy 16–18 . Another recently published meta‐analysis found sarcopenia was only significantly associated with overall morbidity and had no effect on overall mortality or major morbidity (CD3‐5) 56 .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This is at odds with recently published meta‐analyses that show that preoperative sarcopenia is an independent unfavorable prognostic factor for oesophageal and gastric cancer patients after oesophagectomy and gastrectomy 54,55 . Nevertheless, there is conflicting evidence from multiple studies that, similar to us, have been unable to find an association between sarcopenia and postoperative outcomes in an OG cancer cohort undergoing curative therapy 16–18 . Another recently published meta‐analysis found sarcopenia was only significantly associated with overall morbidity and had no effect on overall mortality or major morbidity (CD3‐5) 56 .…”
Section: Discussionmentioning
confidence: 70%
“…During NAT, a reduction in skeletal muscle mass is observed, leading to an increase in the rate of sarcopenia 14–18 . Sarcopenia in OG cancer has been associated with increased dose‐limiting chemotherapy toxicity, 14,19 increased circumferential resection margin positivity 18 and increased mortality 15,20 .…”
Section: Introductionmentioning
confidence: 99%
“…The association of visceral obesity and new-onset postoperative atrial dysrhythmia may suggest common pathways relevant to other perfusion-related complications, including AKI. 39 Although severe postoperative complications may impact on oncologic outcomes, postoperative AKI was not found to independently impact OS or DFS. A Clavien-Dindo classification of 3 or greater was; however, significant, consistent with other studies.…”
Section: Discussionmentioning
confidence: 89%
“…[35][36][37][38] Impairments of physical fitness and HRQoL already present before surgery can be further exacerbated by the surgical procedure, adjuvant chemotherapy and persistent malnutrition. 39 It has been observed that impairments of cardiorespiratory fitness persist for up to 2 years after surgical treatment, 40 muscle mass may continue to decline for up to 1 year after treatment, 41 and HRQoL can remain impaired for years. 42 While this again provides a strong rationale for post-surgery rehabilitation the (promising) evidence in this area is so far limited.…”
Section: Rehabilitation For Other Groups Of Patients Undergoing Oncol...mentioning
confidence: 99%